FRI0183 Adherence to Methotrexate in Rheumatoid Arthritis Treated by Practice Vs. Hospital Based Rheumatologists: A Danish Nationwide Cohort Study. (10th June 2014) - Bliddal, H.; Eriksen, S.A.; Christensen, R.; Lorenzen, T.; Hansen, M.S.; Østergaard, M.; Dreyer, L.; Vestergaard, P.
Abstract : Background: Adherence to Methotrexate has been reported to be weak in patients with rheumatoid arthritis. Objectives: To study adherence to methotrexate (MTX) and factors of importance thereof. in rheumatoid arthritis (RA). Methods: Danish Nationwide cohort study. All patients with a hospital diagnosis of RA (ICD10 codes M05.X, M06.X) after January 1, 1997 and aged ≥18 years at the date of first diagnosis/contact, with at least one prescription of MTX (L04AX03) were included. To avoid prevalent cases only those with a first time diagnosis after January 1, 1998 were included. Results: A total of 18, 703 patients had ever used MTX among 39, 286 with a diagnosis of RA, and among these, 16, 503 had filed more than one MTX prescription. Among MTX users, 48% had been exposed to systemic corticosteroids within the last year prior to first MTX prescription. Time from diagnosis to first MTX prescription was 1.6±2.4years with no indication of decrease during the period. In those who filed more than one MTX prescription, the mean persistence time for ≥7.5 mg MTX per week was 4, 766 days. The main determinants of non-persistence were female gender, younger age, and time from diagnosis to initiation of MTX (those with more than 1 year of lag time being less compliant). The MTX adherence was the same in patients treated in hospital outpatient clinics or by private practising specialist. Conclusions: Treatment at hospital or in private practice did not influence the adherence to MTX. Non-modifiable factors of importance were gender and age, while adherence to MTX therapy decreased with a longer time lapse between diagnosis and prescription. The present study could not document a quick and consistent use of MTX early after diagnosis, as the recommended aggressive treat-to-target strategy with MTX as anchor drug would suggest. Acknowledgements: We thank the personal and scientific support of Statistics Denmark. Disclosure of Interest: H. Bliddal Grant/research support: Roche, Pfizer, Abbvie, Novo, S. Eriksen: None declared, R. Christensen Grant/research support: Roche, Pfizer, MSD, UCB, T. Lorenzen Grant/research support: Roche, M. Hansen Grant/research support: Roche, M. Østergaard Grant/research support: Abbott, Bristol-Myers Squibb, Centocor, GlaxoSmithKline, Janssen, Merck, Mundipharma, Novo Nordisk, Pfizer, Schering-Plough, Roche UCB, L. Dreyer: None declared, P. Vestergaard: None declared DOI: 10.1136/annrheumdis-2014-eular.5585